m+2n+-2m+3n=0

Simple and best practice solution for m+2n+-2m+3n=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+2n+-2m+3n=0 equation:


Simplifying
m + 2n + -2m + 3n = 0

Reorder the terms:
m + -2m + 2n + 3n = 0

Combine like terms: m + -2m = -1m
-1m + 2n + 3n = 0

Combine like terms: 2n + 3n = 5n
-1m + 5n = 0

Solving
-1m + 5n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5n' to each side of the equation.
-1m + 5n + -5n = 0 + -5n

Combine like terms: 5n + -5n = 0
-1m + 0 = 0 + -5n
-1m = 0 + -5n
Remove the zero:
-1m = -5n

Divide each side by '-1'.
m = 5n

Simplifying
m = 5n

See similar equations:

| 12x^2y^5= | | (k-1)(x^2+kx+1)=0 | | -2y-1.7=2.3 | | 2x+6y=12y | | -x=.77 | | (2x^2-9x)(2x^2-9x+13)+36=0 | | (2x^2-9x)(2x^2-9x+13)=-36 | | 5y+11x=87 | | 3x=7(7+1) | | 14(x-3)=112 | | (x+7)+(5x-7)+(4x)=180 | | (7x-4)+(3x+8)+(x)=180 | | 4y-37=99 | | 4y-25=79 | | 4y-25=101 | | 6x-40=110 | | -15-x=-17 | | a+4b-3a-2b= | | 4x-12=96 | | 4+12=96 | | 2(u+2)-8u=28 | | -8v+5(v-7)=-20 | | 1y-.75=.5y-9 | | =ax+ay+az | | -77-3=11 | | e^3x(p-1)+p^3e^2y=0 | | 4k+8= | | (3y+12x)(8y-9x)=152 | | X^2+x^3=11-x | | 5x+x=39 | | -14+6b+7-2b=1+b+5b | | x^2+3=x^2+1 |

Equations solver categories